2014
DOI: 10.1007/s00572-014-0601-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation among matsutake ectomycorrhizae in four clones of Pinus sylvestris

Abstract: Tricholoma matsutake is an ectomycorrhizal fungus that forms commercially important mushrooms in coniferous forests. In this study, we explored the ability of T. matsutake to form mycorrhizae with Pinus sylvestris by inoculating emblings produced through somatic embryogenesis (SE) in an aseptic culture system. Two months after inoculation, clones with less phenolic compounds in the tissue culture phase formed mycorrhizae with T. matsutake, while clones containing more phenols did not. Effects of inoculation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Although associations based on in vitro trials can help us to understand the genetic basis of EcM specificity, the extent to which results reflect natural phenomena with ecological significance is unclear. By using cloned material of P. sylvestris, it has been shown that those individuals containing high concentrations of phenolics and bear thick epidermal cell walls have more limited or no association with matsutake mycelium (Vaario et al 2015a). Additional studies using genetically-uniform material should be undertaken to understand the factors regulating the compatibility of EcM fungi with their host plants.…”
Section: Host Specificitymentioning
confidence: 99%
“…Although associations based on in vitro trials can help us to understand the genetic basis of EcM specificity, the extent to which results reflect natural phenomena with ecological significance is unclear. By using cloned material of P. sylvestris, it has been shown that those individuals containing high concentrations of phenolics and bear thick epidermal cell walls have more limited or no association with matsutake mycelium (Vaario et al 2015a). Additional studies using genetically-uniform material should be undertaken to understand the factors regulating the compatibility of EcM fungi with their host plants.…”
Section: Host Specificitymentioning
confidence: 99%
“…Ectomycorrhizal inoculation increased the height of regenerated plantlets of cell line 20-1-7, but this effect was not evident in the other two cell lines. The effects of inoculation on the growth of cell lines varied from cell line to cell line, as reported by Vaario et al (2015). Yamanaka et al (2012) demonstrated that growth did not change immediately after mycorrhizal inoculation, but positive effects on root-to-crown ratio and root density were found at five months after inoculation.…”
Section: Optimal Composition Aba3+peg3+ac2+maltose3mentioning
confidence: 77%
“…Ectomycorrhizal inoculation increased the height of regenerated plantlets of cell line 20-1-7, but this effect was not evident in the other two cell lines. The effects of inoculation on the growth of cell lines varied from cell line to cell line, as reported by Vaario et al. (2015) .…”
Section: Discussionmentioning
confidence: 88%
“…In Japan and Finland, T. matsutake usually grows in pine forests, where it forms a symbiotic relationship via underground hyphae with the roots of Pinus trees, including red pine ( Pinus densiflora ) . In China, especially in southwestern China, Quercus aquifolioides is one of the main host trees of T. matsutake .…”
Section: Introductionmentioning
confidence: 99%
“…underground hyphae with the roots of Pinus trees, including red pine (Pinus densiflora) [8][9][10]. In China, especially in southwestern China, Quercus aquifolioides is one of the main host trees of T. matsutake [11].…”
mentioning
confidence: 99%